Asymmetric structure composite membrane based on metal organic framework and preparation method and application thereof

CN122998997APending Publication Date: 2026-10-30TIANJIN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611497431.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,在处理含抗生素废水时,水体中的有机物(如四环素)易在蒸馏母液中累积或随蒸汽进入产水,引发二次污染风险,这在一定程度上制约了光热膜蒸馏技术的实际应用

Benefits of technology

本发明提供的基于金属有机框架的非对称结构复合膜及制备方法和应用。该制备方法选用含儿茶酚类有机配体的双金属有机框架作为核心光热-催化材料,通过原位生长工艺将其负载于Cu@PVDF-HFP纳米纤维膜表面,并与PVDF-HFP纳米纤维膜和PS纳米纤维膜通过热压复合后,得到兼具光热转换与活化催化功能的PMD复合膜。性能测试结果显示,在1.0kW·m-2光照强度条件下,该基于金属有机框架的非对称结构复合膜蒸馏通量可达1.48kg·m-2·h-1;在连续运行测试中,复合膜通量保持稳定,未出现明显衰减。该NiCo-CAT基纳米纤维复合膜实现了蒸馏产水与污染物降解的协同进行,有望应用于含抗生素水资源化处理中。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998997A_ABST
    Figure CN122998997A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of functional composite membrane, and particularly relates to an asymmetric structure composite membrane based on a metal organic framework, a preparation method and application thereof. The preparation method selects a bimetallic organic framework containing a catechol organic ligand as a core photothermal-catalytic material, loads the bimetallic organic framework on the surface of a Cu@PVDF-HFP nanofiber membrane through an in-situ growth process to obtain a Cu@PVDF-HFP nanofiber membrane loaded with the bimetallic organic framework, and then composites the Cu@PVDF-HFP nanofiber membrane loaded with the bimetallic organic framework, a PVDF-HFP nanofiber membrane and a PS nanofiber membrane through hot pressing to obtain a photothermal membrane distillation composite membrane which has both photothermal conversion and activation catalytic functions. The performance test results show that, in a continuous operation test, the asymmetric structure composite membrane based on the metal organic framework can maintain a relatively stable distillation flux, has an obvious degradation effect on tetracycline drugs, and is expected to be applied to water resource treatment containing tetracycline drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional composite membrane technology, and in particular to asymmetric composite membranes based on metal-organic frameworks, their preparation methods, and applications. Background Technology

[0002] Photothermal membrane distillation (PMD) is a membrane separation technology that utilizes solar energy for seawater desalination and wastewater treatment. It features low energy consumption, high separation efficiency, and the ability to directly utilize solar energy. However, when treating antibiotic-containing wastewater, organic matter (such as tetracycline) in the water can easily accumulate in the mother liquor or enter the permeate with the steam, posing a risk of secondary pollution. This, to some extent, limits the practical application of PMD technology. Tetracycline (TC), a commonly used broad-spectrum antibiotic in clinical practice, is showing an increasing detection rate in aquatic environments, and its long-term presence may pose potential risks to ecosystems and human health. Therefore, developing photothermal catalytic composite membranes that combine efficient distillation permeate production with pollutant degradation has become a current research direction.

[0003] Currently, in most photothermal membrane distillation and pollutant degradation composite systems, the photothermal conversion unit and the catalytic degradation unit are independent and require separate design and loading. This separate design not only increases the difficulty of composite membrane preparation and system cost but may also lead to problems such as reduced solar energy utilization and insufficient contact of catalytic active sites, thus affecting the overall synergistic performance. Advanced oxidation processes based on sulfate radicals have the characteristics of high degradation efficiency and wide applicability. Coupled with photothermal membrane distillation technology, an integrated photothermal-advanced oxidation process catalytic system can be constructed, utilizing photothermal materials to enhance persulfate activation, aiming to simultaneously achieve distillation-based water production and pollutant degradation. For example, existing research has achieved the integration of photothermal conversion and persulfate activation catalytic degradation, providing a reference for the design of such composite membranes. However, existing composite membrane designs are mostly limited to simple physical loading of functional components and have not fully addressed the synergistic matching problem between the local photothermal thermal field and catalytic active sites at the microscale. This structural limitation leads to high mass transfer resistance at the reaction interface, and the heat energy generated by photothermal processes is difficult to be efficiently utilized in situ by the catalytic reaction, resulting in limited exposure and utilization efficiency of catalytic active sites, which is insufficient to meet the needs of practical applications.

[0004] Therefore, how to provide a composite membrane with a highly efficient photothermal-catalytic synergistic effect to simultaneously improve separation efficiency and pollutant degradation performance remains a key technical problem that urgently needs to be solved. Summary of the Invention

[0005] This invention aims to at least solve one of the technical problems existing in related technologies. Therefore, the first objective of this invention is to provide a method for preparing asymmetric composite membranes based on metal-organic frameworks; the second objective is to provide asymmetric composite membranes based on metal-organic frameworks; and the third objective is to provide applications of asymmetric composite membranes based on metal-organic frameworks.

[0006] To achieve the first objective, the technical solution adopted by this invention is as follows: Methods for preparing asymmetric composite membranes based on metal-organic frameworks include: PVDF-HFP was dissolved in a first organic solvent to obtain a PVDF-HFP precursor solution; Among them, PVDF-HFP is polyvinylidene fluoride-hexafluoropropylene; Using the PVDF-HFP precursor solution as the first spinning solution, PVDF-HFP nanofiber membranes are prepared by a first electrospinning process. PS was dissolved in a second organic solvent to obtain a PS precursor solution; PS stands for polystyrene. Using the PS precursor solution as the second spinning solution, PS nanofiber membranes are prepared by a second electrospinning process. The PVDF-HFP nanofiber membrane was etched to obtain a roughened PVDF-HFP nanofiber membrane. The roughened PVDF-HFP nanofiber membrane was sensitized, activated, and copper-plated to prepare a Cu@PVDF-HFP nanofiber membrane. The Cu@PVDF-HFP nanofiber membrane was immersed in a bimetallic organic framework growth solution, and an in-situ growth process was performed on the surface of the copper layer to obtain a Cu@PVDF-HFP nanofiber membrane loaded with a bimetallic organic framework. The bimetallic organic framework growth solution includes a nickel source, a cobalt source, a catechol organic ligand, and a third solvent. The Cu@PVDF-HFP nanofiber membrane loaded with a bimetallic organic framework, the PVDF-HFP nanofiber membrane, and the PS nanofiber membrane are stacked sequentially between two pressure plates to form a three-layer membrane assembly. After hot-pressing the three-layer membrane assembly, an asymmetric composite membrane based on a metal-organic framework is obtained. The hot-pressing composite process involves a pressure of 0.05–0.15 MPa, a temperature of 100–180 °C, and a time of 0.5–2.0 h.

[0007] Preferably, the parameter settings for the first electrospinning process include: The extrusion rate is 0.1–1.5 ml / h, the electric field strength is 20–45 kV, the distance from the needle tip to the collecting device is 10–25 cm, the rotation speed of the collecting device is 100–500 r / min, and the PVDF-HFP nanofibers are arranged along the rotation direction. The parameter settings for the second electrospinning process include: The extrusion rate is 1-5 ml / h, the electric field strength is 15-40 kV, the distance from the needle tip to the collection device is 10-30 cm, the rotation speed of the collection device is 1000-3500 r / min, the PS nanofibers are arranged along the rotation direction, and the axial rotation direction of the collection device is changed by 90 degrees every 3-10 min to change the orientation of the PS nanofibers.

[0008] Preferably, the first organic solvent is a mixed solvent composed of N,N-dimethylformamide and acetone, wherein the volume ratio of N,N-dimethylformamide to acetone is 2:3 to 3:2; and the second organic solvent is N,N-dimethylformamide.

[0009] Preferably, the concentration of the first spinning solution and the concentration of the second spinning solution are each independently 15-25 wt%.

[0010] Preferably, the etching solution used for the etching process is an aqueous solution of N,N-dimethylformamide, and the volume concentration of the N,N-dimethylformamide aqueous solution is 20-90%. The etching process takes 1 to 5 minutes. The sensitizer used in the sensitization treatment was SnCl2; The activator used in the activation treatment was PdCl2; The copper plating solution used in the copper plating process includes copper sulfate, sodium hydroxide, ethylenediaminetetraacetic acid, citric acid, and potassium sodium tartrate. The mass ratio of copper sulfate, sodium hydroxide, ethylenediaminetetraacetic acid, citric acid, and potassium sodium tartrate is (4-6):(7-9):(3-5):(3-5):(3-5). The copper plating process takes 10 to 30 minutes.

[0011] Preferably, the nickel source is nickel acetate tetrahydrate, the cobalt source is cobalt acetate tetrahydrate, and the catechol organic ligand is hexahydroxytriphenylene. The molar ratio of nickel acetate tetrahydrate, cobalt acetate tetrahydrate, and hexahydroxytriphenylene is (0.9–1.1):(0.9–1.1):(0.9–1.1). The third solvent is a mixed solvent composed of N,N-dimethylformamide and water, with a volume ratio of N,N-dimethylformamide to water of 1:8 to 1:10.

[0012] Preferably, the temperature of the in-situ growth process is 80-90°C, and the growth time is 15-25 min.

[0013] Preferably, in the three-layer membrane assembly, the thickness of the Cu@PVDF-HFP nanofiber membrane loaded with a bimetallic organic framework is 10–20 μm, the thickness of the PVDF-HFP nanofiber membrane is 25–35 μm, and the thickness of the PS nanofiber membrane is 80–140 μm.

[0014] To achieve the second objective, the technical solution adopted by this invention is as follows: The asymmetric structure composite membrane based on the metal-organic framework is prepared by any of the above-described methods for preparing asymmetric structure composite membranes based on the metal-organic framework.

[0015] To achieve the third objective, the technical solution adopted by this invention is as follows: Application of asymmetric composite membranes based on metal-organic frameworks in brine desalination and / or catalytic degradation of tetracycline drugs in water.

[0016] The above-described one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects: This invention provides an asymmetric composite membrane based on a metal-organic framework, its preparation method, and its application. The preparation method uses a bimetallic organic framework containing catechol-based organic ligands as the core photothermal-catalytic material. This framework is loaded onto the surface of a Cu@PVDF-HFP nanofiber membrane via in-situ growth. After hot-pressing composite with PVDF-HFP and PS nanofiber membranes, a PMD composite membrane with both photothermal conversion and catalytic activation functions is obtained. Performance test results show that at 1.0 kW·m... -2 Under light intensity conditions, the distillation flux of this asymmetric composite membrane based on a metal-organic framework can reach 1.48 kg·m³. -2 ·h -1 During continuous operation testing, the flux of the composite membrane remained stable without significant attenuation. This NiCo-CAT-based nanofiber composite membrane achieves synergistic distillation of water and degradation of pollutants, and holds promise for application in the treatment of antibiotic-containing water resources.

[0017] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description

[0018] Figure 1 This is a scanning electron microscope (SEM) image of the PVDF-HFP nanofiber membrane provided in Example 1 of the present invention.

[0019] Figure 2This is a SEM image of the PS nanofiber membrane provided in Embodiment 1 of the present invention.

[0020] Figure 3 This is a SEM image of the Cu@PVDF-HFP nanofiber membrane provided in Example 1 of the present invention.

[0021] Figure 4 This is a scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) image of a Cu@PVDF-HFP nanofiber membrane (NiCo-CAT@PH) loaded with a bimetallic organic framework, provided in Example 1 of this invention.

[0022] Figure 5 This is the NiCo-CAT@PH X-ray diffraction (XRD) pattern provided in Embodiment 1 of the present invention.

[0023] Figure 6 This is a SEM cross-sectional image of the asymmetric composite membrane based on a metal-organic framework provided in Embodiment 1 of the present invention.

[0024] Figure 7 These are SEM images of the asymmetric composite membranes based on metal-organic frameworks prepared in Examples 1, 2, 3 and 4 of this invention.

[0025] Figure 8 This is a graph showing the photothermal conversion performance measurement results of the asymmetric composite film based on a metal-organic framework provided in the test examples of this invention; wherein, graph A shows the performance at 1.0 kW·m -2 1.5kW·m -2 2.0kW·m -2 Infrared thermal images of three light intensities at steady state, Figure B shows the image at 1.0 kW·m -2 1.5kW·m -2 2.0kW·m -2 Temperature variation over time under three light intensities.

[0026] Figure 9 The results of the tetracycline retention performance of the asymmetric composite membrane based on the metal-organic framework provided in the test examples of this invention are as follows. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. The following embodiments are used to illustrate this invention, but cannot be used to limit the scope of this invention.

[0028] In the following embodiments, unless otherwise specified, the experimental methods used are conventional methods, and the materials and reagents used are commercially available, unless otherwise specified, and are carried out in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions.

[0029] Example 1 I. Preparation of PVDF-HFP nanofiber membrane, including the following steps: Step 1: Prepare the first spinning solution.

[0030] Measure 3 mL of N,N-dimethylformamide (DMF) and 2 mL of acetone into a beaker and mix them thoroughly by magnetic stirring to obtain a mixed solvent system with a volume ratio of 3:2. Then, add PVDF-HFP powder to the mixed solvent, controlling its mass fraction to 20 wt%. Place the prepared mixture at room temperature (about 25°C) and continuously stir magnetically for 3 hours until the polymer is completely dissolved, obtaining a clear and transparent PVDF-HFP precursor solution, which is the first spinning solution.

[0031] Step 2: Prepare PVDF-HFP nanofiber membranes using the first electrospinning process.

[0032] The parameter settings for the first electrospinning process are as follows: The extrusion pump has an extrusion rate of 0.5 mL / h, the high-voltage power supply has an operating voltage of 35 kV, the distance between the roller collector and the needle tip is 15 cm, the collection device rotates at a speed of 100 r / min, the relative humidity of the air is 50 ± 5%, and the temperature is about 20℃.

[0033] Under the set process parameters, PVDF-HFP nanofiber membranes, denoted as PVDF-HFP NMs, were successfully prepared. Their SEM images are shown below. Figure 1 As shown in the figure, the nanofiber membrane has a relatively uniform fiber distribution with a fiber diameter of 190±20nm and a dendritic microstructure.

[0034] II. Preparation of PS nanofiber membranes, including the following steps: Step 1: Prepare the PS precursor solution.

[0035] Weigh an appropriate amount of PS particles and add them to DMF (5 mL). Stir continuously until the PS particles are completely dissolved to prepare a PS precursor solution with a mass fraction of 18 wt%, uniform texture, and transparency.

[0036] Step 2: Prepare PS nanofiber membranes using the second electrospinning process.

[0037] The prepared PS precursor solution was loaded into a syringe, and a PS nanofiber membrane was prepared using a second electrospinning process. During the spinning process, the syringe needle was controlled to reciprocate along the axis of the receiving device. To construct a cross-shaped nanofiber structure, the substrate on the receiving roller was rotated 90° axially every 5 minutes. Finally, a PS nanofiber membrane with a simulated cross-shaped microstructure was obtained, as shown in the SEM image. Figure 2 As shown.

[0038] The parameter settings for the second electrospinning process are as follows: The extrusion rate of the spinning solution was 2.5 mL / h, the electric field strength was 25 kV, the distance between the needle tip and the receiving roller was 15 cm, the rotation speed of the receiving roller was 2500 r / min, the experimental environment temperature was controlled at 20±5℃, and the relative humidity of the air was 50±5%.

[0039] III. Preparation of Cu@PVDF-HFP nanofiber membranes.

[0040] The PVDF-HFP NMs membrane is etched to increase the fiber surface area. Subsequently, the etched membrane is sensitized, activated, and copper-plated to obtain a Cu@PVDF-HFP nanofiber membrane, denoted as Cu@PVDF-HFP NMs. The specific steps include the following: Step 1: Clean the PVDF-HFP NMs.

[0041] PVDF-HFP NMs were immersed in a mixed aqueous solution containing 20 g / L sodium carbonate and 15 g / L trisodium phosphate at 55 °C for 10 min, and then rinsed with water to obtain clean PVDF-HFP NMs.

[0042] Step 2: After etching the clean PVDF-HFP NMs with a 50% DMF aqueous solution for 3 minutes, roughened PVDF-HFP NMs are obtained.

[0043] Step 3: Sensitize the roughened PVDF-HFP NMs in a SnCl2 aqueous solution with a concentration of 12 g / L for 4 min. Then, rinse the sensitized membrane with water to obtain sensitized PVDF-HFP NMs.

[0044] Step 4: Place the sensitized PVDF-HFP NMs in a 0.5 g / L PdCl2 aqueous solution and activate it at room temperature (about 25 °C) for 3 min to obtain activated PVDF-HFP NMs.

[0045] Step 5: At room temperature (approximately 25°C), the activated PVDF-HFP NMs were immersed in an aqueous solution containing 125 g / L copper sulfate, 200 g / L sodium hydroxide, 100 g / L EDTA, 100 g / L citric acid, and 100 g / L potassium sodium tartrate for 15 minutes to deposit copper on the membrane surface. After copper deposition, the membrane was rinsed with deionized water to obtain Cu@PVDF-HFP nanofiber membrane. Its SEM image is shown below. Figure 3 As shown in the figure, it can be seen that the diameter of the copper-plated fiber film is increased compared with that of the unplated film, with an average fiber diameter of 380±20nm.

[0046] IV. Preparation of Cu@PVDF-HFP nanofiber membranes loaded with bimetallic organic frameworks, including the following steps: Step 1: Prepare a bimetallic organic framework (NiCo-CAT) growth solution using nickel and cobalt as metal sources and hexahydroxytriphenylene (CAT) as an organic ligand. The solvent is a mixture of DMF and deionized water (H2O) in a volume ratio of 1:9. The solute concentrations are 5 mmol / L nickel acetate tetrahydrate, 5 mmol / L cobalt acetate tetrahydrate, and 5.25 mmol / L catechol organic ligand hexahydroxytriphenylene (CAT). Stir thoroughly until the solutes are completely dissolved to obtain a homogeneous NiCo-CAT bimetallic organic framework growth solution.

[0047] Step 2: Completely immerse the Cu@PVDF-HFP nanofiber membrane in the above-mentioned NiCo-CAT bimetallic organic framework growth solution, and carry out a hydrothermal reaction at a constant temperature of 85℃ for 20 minutes. After the reaction is completed, the Cu@PVDF-HFP nanofiber membrane loaded with the bimetallic organic framework can be obtained, denoted as NiCo-CAT@PH.

[0048] SEM-EDS energy dispersive spectra of NiCo-CAT@PH, as shown Figure 4 As shown, EDS energy dispersive spectroscopy detected characteristic peaks of Ni, Co, and C elements, indicating that Ni and Co have been successfully introduced, realizing the loading of NiCo-CAT on the nanofiber membrane substrate.

[0049] XRD patterns of NiCo-CAT@PH, such as Figure 5 As shown, typical characteristic diffraction peaks of layered conductive MOFs appear at 2θ angles of 5.2°, 9.7°, 17°, 22° and 28°. Among them, the diffraction peaks at 5.2°, 9.7°, 17° and 22° can be attributed to the (100), (200), (300) and (400) crystal planes, respectively, proving that NiCo-CAT@PH has a highly ordered in-plane stacked structure.

[0050] V. Preparation of asymmetric composite membranes based on metal-organic frameworks, the process is as follows: A 15 μm thick NiCo-CAT@PH, a 30 μm thick PVDF-HFP NMs, and a 100 μm thick PS nanofiber membrane were all cut into 5 cm × 5 cm pieces. These were then stacked flat between two clean glass plates (used as pressure plates) and heat-treated at 0.1 MPa pressure and 150 °C for 1 h to complete the hot-pressing composite of the multilayer fiber membranes. This yielded an asymmetric composite membrane based on a metal-organic framework, denoted as NiCo-CAT@PH-TLNMs-PS. Its SEM cross-sectional image is shown below. Figure 6 As shown in the figure, the three-layer membrane interface is tightly bonded, with no delamination or cracking, which ensures the structural stability of the composite membrane during application.

[0051] Example 2 The only difference between the preparation of NiCo-CAT@PH and the preparation of NiCo-CAT@PH in Example 1 is that the volume ratio of DMF to H2O in the NiCo-CAT bimetallic organic framework growth solution is 2:8.

[0052] Example 3 The only difference between the preparation of NiCo-CAT@PH and the preparation of NiCo-CAT@PH in Example 1 is that the volume ratio of DMF to H2O in the NiCo-CAT bimetallic organic framework growth solution is 3:7.

[0053] Example 4 The only difference between the preparation of NiCo-CAT@PH and the preparation of NiCo-CAT@PH in Example 1 is that the volume ratio of DMF to H2O in the NiCo-CAT bimetallic organic framework growth solution is 4:6.

[0054] SEM images of NiCo-CAT@PH prepared in Examples 1, 2, 3, and 4 are shown below. Figure 7As shown in the figure, when the volume ratio of DMF to H2O is 1:9 (corresponding to Example 1), a NiCo-CAT bimetallic organic framework with a regular spiky structure can grow on the surface of the NiCo-CAT@PH fiber, and the active component is uniformly distributed on the fiber surface. When the volume ratio of DMF to H2O is adjusted to 2:8 (corresponding to Example 2), a particulate NiCo-CAT bimetallic organic framework is generated on the fiber surface. Although the loading is high, the particles are irregularly distributed and cover the surface of the nanofiber membrane. When the volume ratio of DMF to H2O is adjusted to 3:7 (corresponding to Example 3) or 4:6 (corresponding to Example 4), the growth of the NiCo-CAT bimetallic organic framework is uneven, and the spiky structure cannot be formed. Based on the above analysis, the optimal volume ratio of DMF to H2O for hydrothermal synthesis of the NiCo-CAT bimetallic organic framework is 1:9.

[0055] Example 5 The preparation of NiCo-CAT@PH-TLNMs-PS differed from Example 1 only in that the thickness of the PS nanofiber membrane was replaced with 140 μm in the hot-pressing composite process.

[0056] Example 6 The preparation of NiCo-CAT@PH-TLNMs-PS differed from Example 1 only in that the thickness of the PS nanofiber membrane was replaced with 120 μm.

[0057] Example 7 The preparation of NiCo-CAT@PH-TLNMs-PS differed from Example 1 only in that the thickness of the PS nanofiber membrane was replaced with 80 μm in the hot-pressing composite process.

[0058] Detection example I. Determination of photothermal conversion performance.

[0059] The effect of light intensity on the photothermal conversion performance of NiCo-CAT@PH-TLNMs-PS (provided in Example 1) was investigated, and tests were conducted at 1.0 kW·m -2 1.5kW·m -2 2.0kW·m -2 The highest temperature achievable by this composite film under three light intensities is as follows: Figure 8 As shown in the figure, the highest surface temperature of the composite film increases significantly with increasing light intensity. Combined with the aforementioned morphology and structural characterization results, it can be concluded that the NiCo-CAT@PH layer on the surface of NiCo-CAT@PH-TLNMs-PS effectively enhances the light-harvesting ability of the material, thereby significantly improving the photothermal conversion efficiency.

[0060] II. Determination of permeation flux and retention performance.

[0061] At 1.0 kW·m -2 Under light intensity, the permeation flux and salt rejection performance of NiCo-CAT@PH-TLNMs-PS provided in Examples 1 and 5-7 were tested for 10 hours continuously. The test results are as follows: The average permeation flux of NiCo-CAT@PH-TLNMs-PS prepared in Examples 1 and 5-7 was 1.48 kg·m³. -2 ·h -1 0.9 kg·m -2 ·h -1 1.24 kg·m -2 ·h -1 and 1.58 kg·m -2 ·h -1 Among them, the salt rejection rates of the composite membranes prepared in Examples 1, 5, and 6 were all higher than 99.99%, while the salt rejection rate of the composite membrane prepared in Example 7 was only 95%. The results show that when the thickness of the PS nanofiber membrane increases from 100 μm to 140 μm, the permeation flux gradually decreases. This is because the thicker PS substrate prolongs the diffusion path of water vapor from the membrane surface to the condensation side, which can significantly increase the mass transfer resistance. Within this thickness variation range, the salt rejection rate of NiCo-CAT@PH-TLNMs-PS can be maintained above 99.9%.

[0062] III. Determination of tetracycline degradation rate.

[0063] The NiCo-CAT@PH-TLNMs-PS composite membrane prepared in Example 1 was tested using a direct-contact photothermal film distillation apparatus. First, it was pre-run for 30 minutes under the following conditions: feed flow rate of 0.29 L / min. -1 The concentration of the feed solution NaCl aqueous solution is 35 g / L, and the light intensity is 1.0 kW·m. -2 The effective test area of ​​the membrane was 2cm × 2cm. The feed solution was then replaced with 500mL of a mixed aqueous solution containing 35g / L NaCl and 50ppm tetracycline, while keeping other operating conditions unchanged. The permeate after membrane separation was collected, and the absorbance of the feed solution and the filtered solution were measured by ultraviolet spectrophotometry. The absorbance was converted to concentration, and the tetracycline rejection rate of the composite membrane was calculated. The test results are as follows: Figure 9 As shown; where C0 is the tetracycline concentration in the initial feed solution; C is the tetracycline concentration in the permeate during the test.

[0064] from Figure 9 It can be seen that the NiCo-CAT@PH-TLNMs-PS composite membrane exhibits excellent photocatalytic degradation effect on tetracycline; while maintaining a permeation flux of 1.48 kg·m³, it achieves this effect.-2 ·h -1 Under these conditions, the degradation rate of tetracycline in the feed system can reach over 99% within 4 hours.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing asymmetric composite membranes based on metal-organic frameworks, characterized in that, include: PVDF-HFP was dissolved in a first organic solvent to obtain a PVDF-HFP precursor solution; Among them, PVDF-HFP is polyvinylidene fluoride-hexafluoropropylene; Using the PVDF-HFP precursor solution as the first spinning solution, PVDF-HFP nanofiber membranes are prepared by a first electrospinning process. PS was dissolved in a second organic solvent to obtain a PS precursor solution; PS stands for polystyrene. Using the PS precursor solution as the second spinning solution, PS nanofiber membranes are prepared by a second electrospinning process. The PVDF-HFP nanofiber membrane was etched to obtain a roughened PVDF-HFP nanofiber membrane. The roughened PVDF-HFP nanofiber membrane was sensitized, activated, and copper-plated to prepare a Cu@PVDF-HFP nanofiber membrane. The Cu@PVDF-HFP nanofiber membrane was immersed in a bimetallic organic framework growth solution, and an in-situ growth process was performed on the surface of the copper layer to obtain a Cu@PVDF-HFP nanofiber membrane loaded with a bimetallic organic framework. The bimetallic organic framework growth solution includes a nickel source, a cobalt source, a catechol organic ligand, and a third solvent. The Cu@PVDF-HFP nanofiber membrane loaded with a bimetallic organic framework, the PVDF-HFP nanofiber membrane, and the PS nanofiber membrane are stacked sequentially between two pressure plates to form a three-layer membrane assembly. After hot-pressing the three-layer membrane assembly, an asymmetric composite membrane based on a metal-organic framework is obtained. The hot-pressing composite process involves a pressure of 0.05–0.15 MPa, a temperature of 100–180 °C, and a time of 0.5–2.0 h.

2. The method for preparing an asymmetric composite membrane based on a metal-organic framework as described in claim 1, characterized in that, The parameter settings for the first electrospinning process include: The extrusion rate is 0.1–1.5 ml / h, the electric field strength is 20–45 kV, the distance from the needle tip to the collecting device is 10–25 cm, the rotation speed of the collecting device is 100–500 r / min, and the PVDF-HFP nanofibers are arranged along the rotation direction. The parameter settings for the second electrospinning process include: The extrusion rate is 1-5 ml / h, the electric field strength is 15-40 kV, the distance from the needle tip to the collection device is 10-30 cm, the rotation speed of the collection device is 1000-3500 r / min, the PS nanofibers are arranged along the rotation direction, and the axial rotation direction of the collection device is changed by 90 degrees every 3-10 min to change the orientation of the PS nanofibers.

3. The method for preparing an asymmetric composite membrane based on a metal-organic framework as described in claim 1, characterized in that, The first organic solvent is a mixed solvent composed of N,N-dimethylformamide and acetone, with a volume ratio of N,N-dimethylformamide to acetone of 2:3 to 3:2; the second organic solvent is N,N-dimethylformamide.

4. The method for preparing an asymmetric composite membrane based on a metal-organic framework as described in claim 1, characterized in that, The concentrations of the first spinning solution and the second spinning solution are each independently 15–25 wt%.

5. The method for preparing an asymmetric composite membrane based on a metal-organic framework as described in claim 1, characterized in that, The etching solution used in the etching process is an aqueous solution of N,N-dimethylformamide, and the volume concentration of the N,N-dimethylformamide aqueous solution is 20-90%. The etching process takes 1 to 5 minutes. The sensitizer used in the sensitization treatment was SnCl2; The activator used in the activation treatment was PdCl2; The copper plating solution used in the copper plating process includes copper sulfate, sodium hydroxide, ethylenediaminetetraacetic acid, citric acid, and potassium sodium tartrate. The mass ratio of copper sulfate, sodium hydroxide, ethylenediaminetetraacetic acid, citric acid, and potassium sodium tartrate is (4-6):(7-9):(3-5):(3-5):(3-5). The copper plating process takes 10 to 30 minutes.

6. The method for preparing an asymmetric composite membrane based on a metal-organic framework as described in claim 1, characterized in that, The nickel source is nickel acetate tetrahydrate, the cobalt source is cobalt acetate tetrahydrate, and the catechol organic ligand is hexahydroxytriphenylene. The molar ratio of nickel acetate tetrahydrate, cobalt acetate tetrahydrate, and hexahydroxytriphenylene is (0.9–1.1):(0.9–1.1):(0.9–1.1). The third solvent is a mixed solvent composed of N,N-dimethylformamide and water, with a volume ratio of N,N-dimethylformamide to water of 1:8 to 1:

10.

7. The method for preparing an asymmetric composite membrane based on a metal-organic framework as described in claim 1, characterized in that, The in-situ growth process is carried out at a temperature of 80–90°C for 15–25 minutes.

8. The method for preparing an asymmetric composite membrane based on a metal-organic framework as described in claim 1, characterized in that, The thickness of the Cu@PVDF-HFP nanofiber membrane loaded with a bimetallic organic framework in the three-layer membrane assembly is 10-20 μm, the thickness of the PVDF-HFP nanofiber membrane is 25-35 μm, and the thickness of the PS nanofiber membrane is 80-140 μm.

9. An asymmetric composite membrane based on a metal-organic framework, characterized in that, It is prepared using the preparation method of the asymmetric structure composite membrane based on the metal-organic framework as described in any one of claims 1 to 8.

10. Application of asymmetric composite membranes based on metal-organic frameworks, characterized in that, The application is the use of the asymmetric structure composite membrane based on the metal-organic framework as described in claim 9 in brine desalination and / or catalytic degradation of tetracycline drugs in water.